Learning Environment of Numeracy: Development and Validation With Confirmatory Factor Analysis and Rasch Model - Mayang Sari, Cynthia; Ridwan, Achmad Ridwan; Sastrawijaya, Yuliatri Sastrawijaya (Pedagogika, 2024)
This study aims to develop and validate an instrument that measures the learning environment of numeracy. The research was conducted in six junior high schools in Central Kalimantan Province in Indonesia. Analysis was conducted using confirmatory factor analysis (CFA) and Rasch model. The results of the analysis showed that 58 items fit the Rasch model and had item and person reliability of 0.99 and 0.98. The instrument has strong psychometric qualities and a decent factor structure.